Localização e Distribuição da Mucosa Olfactiva Humana nas Fossas Nasais - Escada, Pedro (2013)
Introduction: The exact distribution of the human olfactory mucosa can only be determined in studies that evaluate the entire olfactory region. The purpose of this study is to determine the distribution of human olfactory mucosa in the nasal cavities, by performing the histological analysis, by light microscopy, of anatomical specimens of the olfactory region obtained from cadavers. Material and Methods: The specimens were taken during the autopsy of fresh cadavers. In each of the specimens, the distance between the cribiform plate and the lower limit of the olfactory region was determined in three different locations of the septal and lateral walls. Results: Of the 230 anatomical specimens available, 217 were excluded for medical or technical reasons. Morphometric studies were performed on 13 specimens (total 156 measurements). The lower limit of the olfactory mucosa in the nasal septum was 15.9 +/- 3.2 mm, 15.3 mm +/- 3 and 16 +/- 2.8 mm in the anterior, middle and posterior olfactory regions. The lower limit of the olfactory mucosa in the turbinate wall was 15.3 +/- 2.4 mm, 14.8 +/- 2.3 mm and 12.3 +/- 1.9 mm in the equivalent regions. The minimum value observed was 12 mm. Conclusions: The olfactory mucosa extends through the upper and middle turbinates and the confronting nasal septum in a minimum distance of 12 mm and that may exceed 16 mm. Knowing the exact distribution of the olfactory mucosa can guide the collection of this tissues in humans, for diagnostic or therapeutic purposes.